Search for charged Higgs bosons through the violation of lepton universality in t(t)over-bar events using pp collision data at root s=7 TeV with the ATLAS experiment - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
In several extensions of the Standard Model, the top quark can decay into a bottom quark and a light charged Higgs boson H +, t → bH +, in addition to the Standard Model decay t → bW. Since W bosons decay to the three lepton generations equally, while H + maypredominantlydecayinto τν, charged Higgs bosons can be searched for using the violation of lepton universality in top quark decays. The analysis in this paper is based on 4.6 fb-1 of proton-proton collision data at √s=7 TeV collected by the ATLAS experiment at the Large Hadron Collider. Signatures containing leptons (e or μ) and/or a hadronically decaying τ (τ had) are used. Event yield ratios between e + τ had and e + μ, as well as between μ + τ had andμ + e, final states are measured in the data and compared to predictions from simulations. This ratio-based method reduces the impact of systematic uncertainties in the analysis. No significant deviation from the Standard Model predictions is observed. With the assumption that the branching fraction ℬ (H + → τν) is 100%, upper limits in the range 3.2%-4.4% can be placed on the branching fraction ℬ (t → bH +) for charged Higgs boson masses m H+ in the range 90-140 GeV. After combination with results from a search for charged Higgs bosons in t\overline{t} decays using the τ had + jets final state, upper limits on ℬ (t → bH +) can be set in the range 0.8%-3.4%, for m H+ in the range 90-160 GeV.[Figure not available: see fulltext.] © 2013 Cern for the benefit of the ATLAS collaboration.